2011
DOI: 10.1155/2011/125467
|View full text |Cite
|
Sign up to set email alerts
|

The Role of EGFR Inhibitors in the Treatment of Metastatic Anal Canal Carcinoma: A Case Series

Abstract: Anal cancer patients who have exhibited disease progression after having received all approved drugs pose a major therapeutic challenge. In addition to cytotoxic agents, novel targeted agents are being developed and have an established role in the treatment of many solid tumors, including colon cancer. However, their role in anal cancer is yet to be determined. Most anal malignancies are squamous cell carcinomas often strongly expressing epidermal growth factor receptors (EGFRs). Targeting the latter seems to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
0
9
0
3
Order By: Relevance
“…A number of previous studies have demonstrated universal expression of EGFR in anal squamous cell carcinomas [7,8,11] , and several case studies showed clinical efficacy of EGFR inhibitors in patients with metastatic anal cancer [6,[12][13][14][15] . However, these successes with targeting EGFR remain anecdotal due to the limited number of patients in each case study.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have demonstrated universal expression of EGFR in anal squamous cell carcinomas [7,8,11] , and several case studies showed clinical efficacy of EGFR inhibitors in patients with metastatic anal cancer [6,[12][13][14][15] . However, these successes with targeting EGFR remain anecdotal due to the limited number of patients in each case study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, yet another study demonstrated high toxicity of cetuximab therapy [42]. At present, evaluation of any benefit of cetuximab or panitumumab in the therapy of metastatic anal cancer is available mostly in the form of case reports [39,[43][44][45]. As mentioned above, worse tolerance of the therapy is a problem in the combination of antiEGFR therapy and chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…La fréquente surexpression du récepteur de l'EGF et la rareté des mutations de KRAS et de BRAF au niveau tumoral constituent un rationnel pour l'évaluation des agents ciblant le récepteur à l'EGF (EGF-R) dans cette indication [35]. Des résultats encourageants ont été observés avec le cetuximab administré seul ou en association à l'irinotécan chez quelques patients atteints de carcinomes épidermoïdes du canal anal métastatiques, en particulier en l'absence de mutation somatique de KRAS [35][36][37].…”
Section: ❙ Tumeurs De Stade T2/3 N0/3unclassified
“…Des résultats encourageants ont été observés avec le cetuximab administré seul ou en association à l'irinotécan chez quelques patients atteints de carcinomes épidermoïdes du canal anal métastatiques, en particulier en l'absence de mutation somatique de KRAS [35][36][37]. Ils justifient…”
Section: ❙ Tumeurs De Stade T2/3 N0/3unclassified